Real-time Characterization of Antibody Binding to Receptors on Living Immune Cells - Bondza, Sina; Foy, Eleanor; Brooks, Jonathan; Andersson, Karl; Robinson, James; Richalet, Pascale; Buijs, Jos (Frontiers in Immunology, 2017)
Understanding molecular interactions on immune cells is crucial for drug development to treat cancer and autoimmune diseases. When characterizing molecular interactions, the use of a relevant living model system is important, as processes such as receptor oligomerization and clustering can influence binding patterns. We developed a protocol to enable time-resolved analysis of ligand binding to receptors on living suspension cells. Different suspension cell lines and weakly adhering cells were tethered to Petri-dishes with the help of a biomolecular anchor molecule (BAM) and antibody binding was analyzed using LigandTracer. The protocol and assay described in this report were used to characterize interactions involving eight cell lines. Experiments were successfully conducted in three different laboratories, demonstrating the robustness of the protocol. For various antibodies, affinities and kinetic rate constants were obtained for binding to CD20 on both Daudi and Ramos B-cells, the T-cell co-receptor CD3 on Jurkat cells, and the Fc-gamma receptor CD32 on transfected HEK293 cells, respectively. Analyzing the binding of Rituximab to B-cells resulted in an affinity of 0.7-0.9 nM, which is similar to values reported previously for living B-cells. However, we observed a heterogeneous behavior for Rituximab interacting with B-cells, which to our knowledge has not been described previously. The understanding of complex interactions will be facilitated with the possibility to characterize binding processes in real-time on living immune cells. This provides the chance to broaden the understanding of how binding kinetics relate to biological function.